The Ross Procedure in Active Infective Endocarditis: A Comparison With Conventional Prostheses - Hiromu Kehara, MD, PhD; Mohammed Kashem, MD, PhD; Huaqing Zhao, PhD; Sebastian A. Iturra, MD; Suyog A. Mokashi, MD; Ravishankar Raman, MD; Roh Yanagida, MD, PhD; Kewal Krishan, MD; Norihisa Shigemura, MD, PhD; Yoshiya Toyoda, MD, PhD (Annals of Thoracic Surgery Short Reports)
Background: The Ross procedure can be an ideal option in infective endocarditis (IE) due to greater resistance to infection. However, limited literature has highlighted the comparison with conventional prostheses in this setting. Methods: Between February 2013 and September 2022, 25 patients (median age, 50 years) underwent a Ross procedure for IE (Ross group). The results were compared with those after other aortic valve procedures (aortic valve replacement and aortic root replacement) for IE (n = 37, other group. Results: The patients in the Ross group included more intravenous drug users and had more prosthetic valve endocarditis and annular abscess formation compared with the other group. Although cardiopulmonary bypass time and aortic cross-clamp time were significantly longer (P < .001 and P = .003, respectively) and the blood requirements were significantly higher (P = .001) in the Ross group, most postoperative short-term outcomes were equivalent between the 2 groups. During follow-up, 1 patient (4%) required reoperation in the Ross group, whereas 6 patients (16%) required reoperation in the other group. Freedom from composite events was significantly better in the Ross group (P = .04). Multivariable analysis found the Ross procedure, compared with other procedures, was a significant independent protective factor for composite end points (P = .03). Conclusions: For IE, despite surgical complexity, the Ross procedure yielded short-term outcomes similar to other procedures. In the midterm, the Ross procedure provides a lower reoperation rate, resulting in significantly fewer composite events. The Ross procedure appears to be a better option for patients with IE, but long-term follow-up is necessary.